The potential of conservationist use as an instrument for territorial management: a proposal: Article - Gass, Sidnei Luís Bohn; Silva, Dieison Morozoli da; Arruda, Sidney Ferreira de (Geographicalia, 2023)
The municipality is an important unit of territorial planning and management that, despite having defined geographiclimits, demands complex management work. The present work aimed to present a proposal for using the PCU methodology for territorial planning purposes, comparing it with other data that could contribute to its refinement, taking the municipality of Itaqui, RS, Brazil as a laboratory. Slope, lithology and pedology data relating to the study area, combined through map algebra, resulted in the spatialization of the PCU. The following were identified in the municipality: 0.19% of very low PCU; 4.63% low;37.07% average; 47.31% high and 10.81% of areas with very high PCU. The smallest PCU were mostly located close to the main watercourses, while the areas with medium PCU are located in the floodplains of the main rivers. The data obtained was in agreement with pre-existing mappings, having potential for new studies, with greater refinements.
Keywords: Itaqui; soils; planning; agriculture; AHP